The Effect of Small Group Discussion (SGD) to Increase Students’ Writing Ability in Asistensi Mengajar Program at SMPN 04 Kendari - Anisa Alwi, Nur; Amin, Syarif; Faridawati (Mataoleo: Journal of English Education and Linguistics, 2025)
The purpose of this study is to determine whether small group discussions (SGD) can improve students write personal recount text with good generic structure in class VIII/6 Kendari. After carried out the teaching and learning process on personal recount text material individually, students are still lacking to write their experiences into the good generic structure. The subjects were chosen purposively all students from class VIII/6, a total of 30 students. This study employed the Classroom Action Research (CAR) method, in which researcher carried out teaching and learning activities in class. This research was carried out in two cycles of four meetings, with four meetings carried out using the cooperative learning model Small Group Discussion (SGD), and at the end of each cycle, an evaluation test was performed for each group of students. The findings of this study show that the presentation of student achievement is 96% and the average score is 100% when Small Group Discussion (SGD) is used in Cycle 2. This study concluded that implementing small group discussion (SGD) in learning to write English in class, particularly on the ability to write personal recount text with good generic structure, has a significant impact on improving learning outcomes